(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This article is structured from the look we have given to the socioenvironmental aspects analyzed from interviews with recyclable material collectors. We infer how these are observed concerning to the environment and also how they are seen within it, contextualizing the socioenvironmental aspects having regard to the concepts of critical environmental education, based on the surveying on the opinions and perceptions of the interviewed collectors. This is a qualitative research that had as participants five collectors who were present at the VI Expo Catadores, São Paulo. Among the results, we observed that they have, in this work activity, the only way to ensure survival for them and their families. However, in spite of the importance of work, in the speeches of these subjects, the economic impact of recycling is seldom adequately estimated, because considered as an activity "without structuring", is the essential step for strengthening the category, which is organized in cooperatives of waste collectors and associations.